2018
DOI: 10.1080/08897077.2017.1391925
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime Marijuana and Alcohol use, and Cognitive Dysfunction in People with Human Immunodeficiency virus Infection

Abstract: Current marijuana use was associated with one measure of cognitive dysfunction, but there was not a consistent pattern of association with lifetime marijuana use or alcohol use and measures of cognitive dysfunction. Understanding the mechanism by which marijuana, with and without alcohol, are associated with worse cognition warrants larger, longer studies with more precise and diverse measurements of cognitive function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 48 publications
(114 reference statements)
0
7
1
Order By: Relevance
“…Our findings of significant associations between current monthly and daily marijuana use with slowed cognitive processing speed differ from other studies of HIV+ individuals that found no significant associations (Chang et al, 2006;Cristiani et al, 2004;Lorkiewicz et al, 2017;Thames et al, 2017Thames et al, , 2015. For instance, Thames et al (2015) in a small crosssectional study of 89 HIV+ and HIV-subjects found that HIV+ subjects with moderate-toheavy marijuana use (i.e., 18 −90 times per week in the past year) demonstrated no significant associations with slowed processing speed than none-users (Thames et al, 2015).…”
Section: Current Marijuana Use and Cognitioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our findings of significant associations between current monthly and daily marijuana use with slowed cognitive processing speed differ from other studies of HIV+ individuals that found no significant associations (Chang et al, 2006;Cristiani et al, 2004;Lorkiewicz et al, 2017;Thames et al, 2017Thames et al, , 2015. For instance, Thames et al (2015) in a small crosssectional study of 89 HIV+ and HIV-subjects found that HIV+ subjects with moderate-toheavy marijuana use (i.e., 18 −90 times per week in the past year) demonstrated no significant associations with slowed processing speed than none-users (Thames et al, 2015).…”
Section: Current Marijuana Use and Cognitioncontrasting
confidence: 99%
“…In a cross-sectional analysis of 215 HIV+ adults with substance use disorder, lifetime marijuana use, was defined as the number of years marijuana was used ≥3 times per week. Although they did not assessed cognitive processing speed or flexibility, they authors found no significant association between lifetime marijuana use and worse memory and attention assessed using the Montreal Cognitive Assessment (MoCA) (Lorkiewicz et al, 2017). These findings lend support to the literature on residual effects of marijuana exposure on cognitive function, which suggest that cognitive deficits dissipate following abstinence periods that span 25 days (Gonzalez, 2007;Grant et al, 2003;Schreiner & Dunn, 2012).…”
Section: Cumulative Marijuana Use and Cognitionmentioning
confidence: 70%
“…However, in this cohort, total lifetime alcohol consumption and years of very heavy drinking were highly correlated, making the distinction between total consumption and drinking pattern less relevant. [ 81 ]…”
Section: Discussionmentioning
confidence: 99%
“…Cannabis disturbs cognition acutely, but its longer-term effects on brain function in HIV are not well understood. While there is limited evidence of increased cognitive impairment in some cannabis-using PWH [ 127 , 128 ], chronic exposure may also reduce inflammation [ 67 ], possibly resulting in improved CNS outcomes among PWH. Still, the degree and pattern of cannabis exposure that may be therapeutic, neutral, or harmful is not understood.…”
Section: Cannabinoids and Inflammation In The Brain In Hivmentioning
confidence: 99%